DEVELOPMENT OF PROTEIN FOAMER TECHNOLOGY FOR USE IN SPORTS NUTRITION - Krumlikov V.Y.; Izgarysheva N.V.; Pozo-Dengra J.; Kriger O.V. (Техника и технология пищевых производств)
In this paper, on the basis of the conducted research, the technology of foaming agent for sports nutrition from pig blood has beendeveloped. The formulae of presented options of products are given. Physico-chemical properties and microbiological characteristics have been studied. The process of obtaining a foaming agent consists of the following operations: blood collection, stabilization of blood, cooling of stabilized blood, and separation of plasma and eritrocitarnae mass, collection of plasma, freeze-drying, packaging, storage. To stabilize whole blood, it is advisable to use a 0.75% solution of Na3PO4 and 4% solution of Na3C6 H5O7 in the ratio of 1:1 or a 0.75% solution of Na3PO4 and 4% solution of Na3C6 H5O7, in the ratio of 2:3. The stabilizer to blood ratio is 1:10. The separation of stabilized blood is made when the separation factor Fr =2000. Blood plasma drying is carried out using a sublimation method. The total process lasts for 240 minutes at the temperature of 40C. The developed technology allows obtaining a finished product that meets the requirements of SanRaN for microbiological characteristics and the content of toxic elements. The product has a high content of essential amino acids and can be recommended as a protein component of the protein cocktails for sports nutrition. Production of protein foam concentrates with a high content of protein from secondary raw materials (pig blood plasma) is a good way to improve the quality of functional foods using a low cost process.